Comparative Anatomical Study of Fruit and Seeds of Six Species within Selected Six Genera of the Family Fabaceae Lindl. In Iraq - Serwan T. S. Al-dabbagh; Firas Dh. Y. Al-Otraqche; Sumaiah I. Hamad; Mahmood P. Kareem (Zanco Journal of Pure and Applied Sciences, 2023)
The fruit and seeds of six species within six genera belonging to the Fabaceae family were studied. The paraffine methods were applied to microscopic studies. The study showed different fruit outline shapes, the fruiting layers were varying among them, however, all fruits consisted of three layers the exocarp, mesocarp, and endocarp. The thickness of pericarp layers was different in all species. The seed contents were examined, the testa tissue was described and the embryo shape and position were determined.